Gas Sensors: Enhanced Gas Sensing Performance of Organic Field‐Effect Transistors by Modulating the Dimensions of Triethylsilylethynyl‐Anthradithiophene Microcrystal Arrays (Adv. Mater. Interfaces 4/2020). Issue 4 (21st February 2020) - Kwak, Do Hun; Seo, Yena; Anthony, John E.; Kim, Seunghyun; Hur, Jiyeon; Chae, Huijeong; Park, Hui Joon; Kim, Bong‐Gi; Lee, Eunho; Ko, Sunglim; Lee, Wi Hyoung
Abstract : In article number 1901696, Wi Hyoung Lee and co‐workers report a method to increase sensitivity of the 5, 11‐bis(triethylsilylethynyl)‐anthradithiophene (TES‐ADT) gas sensors by adopting TES‐ADT crystal arrays of various shapes and dimensions. The patterning and crystallization of spin‐cast TES‐ADT films are simultaneously achieved by the use of a solvent‐containing engraved polydimethylsiloxane mold. The increased sensing performance in patterned TES‐ADT film is mainly due to the increased area of crystal edges, which provides a diffusion pathway for gas molecules to arrive at the semiconductor‐dielectric interface.